Influence of iron manipulation on hypoxic pulmonary vasoconstriction and pulmonary reactivity during ascent and acclimatization to 5050 m. (3rd February 2021) - Willie, Christopher K.; Patrician, Alexander; Hoiland, Ryan L.; Williams, Alexandra M.; Gasho, Christopher; Subedi, Prajan; Anholm, James; Drane, Aimee; Tymko, Michael M.; Nowak‐Flück, Daniela; Plato, Sawyer; McBride, Emily; et al.
Abstract : Key points: Iron acts as a cofactor in the stabilization of the hypoxic‐inducible factor family, and plays an influential role in the modulation of hypoxic pulmonary vasoconstriction. It is uncertain whether iron regulation is altered in lowlanders during either (1) ascent to high altitude, or (2) following partial acclimatization, when compared to high‐altitude adapted Sherpa. During ascent to 5050 m, the rise in pulmonary artery systolic pressure (PASP) was blunted in Sherpa, compared to lowlanders; however, upon arrival to 5050 m, PASP levels were comparable in both groups, but the reduction in iron bioavailability was more prevalent in lowlanders compared to Sherpa. Following partial acclimatization to 5050 m, there were differential influences of iron status manipulation (via iron infusion or chelation) at rest and during exercise between lowlanders and Sherpa on the pulmonary vasculature. Abstract: To examine the adaptational role of iron bioavailability on the pulmonary vascular responses to acute and chronic hypobaric hypoxia, the haematological and cardiopulmonary profile of lowlanders and Sherpa were determined during: (1) a 9‐day ascent to 5050 m (20 lowlanders; 12 Sherpa), and (2) following partial acclimatization (11 ± 4 days) to 5050 m (18 lowlanders; 20 Sherpa), where both groups received an i.v. infusion of either iron (iron (iii)‐ hydroxide sucrose) or an iron chelator (desferrioxamine). During ascent, there were reductions in iron status in both lowlanders and Sherpa; however, Sherpa appeared to demonstrate a more efficient capacity to mobilize stored iron, compared to lowlanders, when expressed as a Δhepcidin per unit change in either body iron or the soluble transferrin receptor index, between 3400–5050 m ( P  = 0.016 and P  = 0.029, respectively). The rise in pulmonary artery systolic pressure (PASP) was blunted in Sherpa, compared to lowlanders during ascent; however, PASP was comparable in both groups upon arrival to 5050 m. Following partial acclimatization, despite Sherpa demonstrating a blunted hypoxic ventilatory response and greater resting hypoxaemia, they had similar hypoxic pulmonary vasoconstriction when compared to lowlanders at rest. Iron‐infusion attenuated PASP in both groups at rest ( P  = 0.005), while chelation did not exaggerate PASP in either group at rest or during exaggerated hypoxaemia ( P I O 2  = 67 mmHg). During exercise at 25% peak wattage, PASP was only consistently elevated in Sherpa, which persisted following both iron infusion or chelation. These findings provide new evidence on the complex interplay of iron regulation on pulmonary vascular regulation during acclimatization and adaptation to high altitude. Key points: Iron acts as a cofactor in the stabilization of the hypoxic‐inducible factor family, and plays an influential role in the modulation of hypoxic pulmonary vasoconstriction. It is uncertain whether iron regulation is altered in lowlanders during either (1) ascent to high altitude, or (2) following partial acclimatization, when compared to high‐altitude adapted Sherpa. During ascent to 5050 m, the rise in pulmonary artery systolic pressure (PASP) was blunted in Sherpa, compared to lowlanders; however, upon arrival to 5050 m, PASP levels were comparable in both groups, but the reduction in iron bioavailability was more prevalent in lowlanders compared to Sherpa. Following partial acclimatization to 5050 m, there were differential influences of iron status manipulation (via iron infusion or chelation) at rest and during exercise between lowlanders and Sherpa on the pulmonary vasculature.